1993
DOI: 10.2105/ajph.83.8.1113
|View full text |Cite
|
Sign up to set email alerts
|

Oral contraceptives and the risk of gallbladder disease: a meta-analysis.

Abstract: OBJECTIVES. This study was designed to assess the risk of gallbladder disease due to oral contraceptive use by conducting a thorough literature review. METHODS. Controlled epidemiologic studies published through March 1992 were systematically searched and evaluated. Of 25 studies (27 publications), 9 could stand the test of critical appraisal with respect to validity. Restriction to these studies was judged to circumvent publication bias at the same time. RESULTS. Oral contraceptive use is associated with a sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 32 publications
1
26
1
Order By: Relevance
“…2 Population-based studies have revealed a marked variation in the prevalence of GBD among different racial/ethnic groups, and the prevalence is highest among American Indian and Hispanic women and lowest among non-Hispanic black men. 2,30 In addition to age, sex, and race/ethnicity, other potential risk factors for GBD include obesity, 2,31 rapid weight loss, 31 lower levels of physical activity, 2,32 pregnancy, 33 increasing number of live births, 2 oral contraceptive use and estrogen replacement therapy, 34,35 diabetes mellitus, 2,36 abstinence from alcohol, 2,37 smoking, 2 low total serum cholesterol levels, 2,16 low levels of coffee consumption, 38,39 and genetic factors. 40 However, some of these variables have not been consistently associated with GBD, and these risk factors may differ considerably among men and women.…”
Section: Discussionmentioning
confidence: 99%
“…2 Population-based studies have revealed a marked variation in the prevalence of GBD among different racial/ethnic groups, and the prevalence is highest among American Indian and Hispanic women and lowest among non-Hispanic black men. 2,30 In addition to age, sex, and race/ethnicity, other potential risk factors for GBD include obesity, 2,31 rapid weight loss, 31 lower levels of physical activity, 2,32 pregnancy, 33 increasing number of live births, 2 oral contraceptive use and estrogen replacement therapy, 34,35 diabetes mellitus, 2,36 abstinence from alcohol, 2,37 smoking, 2 low total serum cholesterol levels, 2,16 low levels of coffee consumption, 38,39 and genetic factors. 40 However, some of these variables have not been consistently associated with GBD, and these risk factors may differ considerably among men and women.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that estrogen has a critical role in the pathogenesis of cholesterol cholelithiasis because gallstone prevalence is markedly higher in women than in men at all ages in every population studied ( 2 ). Many clinical studies have found that the use of oral contraceptives and conjugated estrogens in premenopausal and postmenopausal women signifi cantly increases the prevalence of gallstones (3)(4)(5). Because elevated estrogen levels have a linear and positive relationship with the duration of gestation, the risk of gallstone formation becomes higher in the third trimester of pregnancy ( 6 ).…”
mentioning
confidence: 99%
“…5 Similarly, a meta-analysis of 26 observational studies found a 36% increase in the development of gallbladder disease among women who were using oral contraceptives compared with those not taking these drugs. 4 Both estrogen and pro gesterone have been shown to increase the risk of gallstones. 12 Estrogen has been shown to increase cholesterol production in the liver, with excess amounts precipitating in bile and leading to the formation of gallstones.…”
Section: Discussionmentioning
confidence: 99%
“…8 If there were a substantial risk of gallbladder disease with drospirenone, this might influence its overall risk-benefit ratio and could prompt physicians to prescribe safer alternatives. Given that women using oral contraceptives have been found to be at increased risk of gallbladder disease compared with women not using oral contraceptives, 4 any excess risk associated with the use of drospirenone merits quantification within the context of a comparative safety study.…”
mentioning
confidence: 99%